Earth observations from space : the first 50 years of scientific achievements (National Academies Press, 2008)
Over the past 50 years, thousands of satellites have been sent into space on missions to collect data about the Earth. Today, the ability to forecast weather, climate, and natural hazards depends critically on these satellite-based observations. At the request of the National Aeronautics and Space Administration, the National Research Council convened a committee to examine the scientific accomplishments that have resulted from space-based observations. This book describes how the ability to view the entire globe at once, uniquely available from satellite observations, has revolutionized Earth studies and ushered in a new era of multidisciplinary Earth sciences. In particular, the ability to gather satellite images frequently enough to create "movies" of the changing planet is improving the understanding of Earth's dynamic processes and helping society to manage limited resources and environmental challenges. The book concludes that continued Earth observations from space will be required to address scientific and societal challenges of the future.